1999
DOI: 10.1128/mcb.19.6.4121
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repressor ERF Is a Ras/Mitogen-Activated Protein Kinase Target That Regulates Cellular Proliferation

Abstract: A limited number of transcription factors have been suggested to be regulated directly by Erks within the Ras/mitogen-activated protein kinase signaling pathway. In this paper we demonstrate that ERF, a ubiquitously expressed transcriptional repressor that belongs to the Ets family, is physically associated with and phosphorylated in vitro and in vivo by Erks. This phosphorylation determines the ERF subcellular localization. Upon mitogenic stimulation, ERF is immediately phosphorylated and exported to the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
146
1
16

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(176 citation statements)
references
References 53 publications
13
146
1
16
Order By: Relevance
“…ERF has been shown to be important for the G 1 transition, and has been shown to enter the nucleus at specific stages of the cell cycle. 24 The FLI1/ERF protein demonstrates a similar mitogen-activated protein kinase-dependent subcellular localization, suggesting that temporary entry of the FLI1/ERF protein into the nucleus is sufficient to suppress the ES phenotype. Because FLI1/ERF and EWS/FLI1 have opposite effects on transcription, the oncogenic activity of the EWS/FLI1 fusion protein is likely to involve activation of genes that can promote or allow inappropriate progression into the G 1 phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ERF has been shown to be important for the G 1 transition, and has been shown to enter the nucleus at specific stages of the cell cycle. 24 The FLI1/ERF protein demonstrates a similar mitogen-activated protein kinase-dependent subcellular localization, suggesting that temporary entry of the FLI1/ERF protein into the nucleus is sufficient to suppress the ES phenotype. Because FLI1/ERF and EWS/FLI1 have opposite effects on transcription, the oncogenic activity of the EWS/FLI1 fusion protein is likely to involve activation of genes that can promote or allow inappropriate progression into the G 1 phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Both inhibition of Erk activity as well as introduction of mutations that affect the ERF subcellular localization can generate a range of repressors with increased nuclear localization and thus increased repressor activity. 24 It has been suggested that "the ideal cancer therapy would accommodate the specific biology of a tumor and be based on understanding the mechanisms of malignancy." 45 In this sense, ERF repressor hybrids, with the unique potential to be regulated both quantitatively and by extracellular signals, may be an approach that could be valuable in the ES system, as well as other systems that involve inappropriate transcription factor activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations